Визначення економічних параметрів виконання проєктів, представлених мережею взаємопов’язаних робіт - Закутній, С. В. (ХНУРЕ, 2023)
The work is dedicated to researching the economic parameters of a project represented by a set of interconnected tasks using graph theory and fuzzy set theory. The work will consider an algorithm that will allow solving the problem of project task planning and evaluating its execution progress, as well as attempting to predict the possible time of completion of this project in the presence of fuzzy estimates of task execution. As a result, it will be necessary to obtain an optimal plan for project development, as well as determine the time of completion of this plan.
Keywords: мережеве планування; економічні параметри проєкту; мережевий граф; оптимальний план створення сайту